Wulff’s Model as a Framework to Evaluate the Quality of Nursing Doctoral Education - Atiyeh, Huda; Nabolsi, Manar; Bani Hani, Manar; Alslman, Eman (DIRASAT: EDUCATIONAL SCIENCES, 2019)
Evaluation of doctoral education is a major concern in higher education institutions, and it is one of the research priorities in Jordan determined by the Higher Council for Science & Technology for the Years 2011-2020. This paper suggested a proposed model derived from Wulff's Alignment Model and the integration of the Quality of Nursing Doctoral Education (QNDE) questionnaire as a formative assessment. This assessment included four domains; program features, faculty members, resources and evaluation. These four domains were assessed through the alignment of the students’, graduates,’ and faculty perspectives. Aligning these perspectives will shed the light on improvement opportunities.